Critical Care in Obstetrics: Where are We - Chawla, Sushil (J Obstet Gynaecol India, 2018)
Maternal mortality is disastrous news for the society, family, newborn, and the obstetrician. Yet, we all who are care providers to these apparently healthy women carrying another life within them are dumbfounded by the clinical conditions arising due to the pregnancy or the effects of the pregnancy, that it becomes difficult to provide an ideal care to them. The rapid uprising of a condition and the worsening of commonly occurring benign conditions—preeclampsia, hemorrhage, etc., necessitates that all obstetricians are well versed with the physiological changes and should be able to not only provide the best of obstetric care to the mother and the newborn but also perform or assist in performance of life-saving procedures.